Designing and Experimenting the Innovative, Alternative and Complimentary Wireless Communication Technique Used For the IOT Application: Exploring wireless communication technologies for IoT applications (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Internet of Things (IoT) is a new computing worldview that visualizes changing over regular common articles into keen items. Wireless technologies will be the most ideal choice to associate IoT devices on account of its advantages over wired technologies including simpler establishment, cheaper frameworks, portability backing, adaptability, and simplicity of association. There are various types of wireless technologies applicable for IoT these technologies range various spaces from not many centimeters to numerous kilometers. In this paper the Internet Engineering Task Force (IETF) presented 6LowPAN protocol and ZigBee union created ZigBee protocol over low power IEEE802.15.4 protocol. Sensors in wireless sensor networks applications are assembled as bunches to inform hubs called sensor hubs. These hubs are typically powered by battery power supply. In IoT applications these hubs should do its capacity for years without change their batteries. IoT helps making choices upheld by real data gathered utilizing large number of ordinary day-to-day devices that have been augmented with knowledge through the installation of detecting, processing and communication capabilities. IoT devices mainly utilize wireless communication for communicating with different devices.